2022
DOI: 10.3390/antiox11050974
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Effect of Natural Antimicrobials in Shrimp Primary Intestinal Cells Infected with Nematopsis messor

Abstract: Nematopsis messor infections severely impact on shrimp’s health with devastating economic consequences on shrimp farming. In a shrimp primary intestinal cells (SGP) model of infection, a sub-inhibitory concentration (0.5%) of natural antimicrobials (Aq) was able to reduce the ability of N. messor to infect (p < 0.0001). To prevent N. messor infection of SGP cells, Aq inhibits host actin polymerization and restores tight junction integrity (TEER) and the expression of Zo-1 and occluding. The oxidative burst,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…The plates were gently centrifuged at 250× g for 5 min and incubated for a further 3 h. The cell-associated bacteria were estimated by washing the infected monolayers (3×) with PBS followed by exposure to 0.1% Triton X-100 in PBS for 15 min at 41.5 • C and 37 • C. Dilutions (10-fold) of infected or control wells were plated onto TSAYE agar and incubated for 2 days prior to enumeration, at 37 • C. All assays were performed in triplicate and on three separate days. Cytotoxicity of Auraguard was determined as previously described [34] by utilizing the MTT assay (Sigma-Aldrich, Gillingham, England, UK).…”
Section: Infection Assaymentioning
confidence: 99%
“…The plates were gently centrifuged at 250× g for 5 min and incubated for a further 3 h. The cell-associated bacteria were estimated by washing the infected monolayers (3×) with PBS followed by exposure to 0.1% Triton X-100 in PBS for 15 min at 41.5 • C and 37 • C. Dilutions (10-fold) of infected or control wells were plated onto TSAYE agar and incubated for 2 days prior to enumeration, at 37 • C. All assays were performed in triplicate and on three separate days. Cytotoxicity of Auraguard was determined as previously described [34] by utilizing the MTT assay (Sigma-Aldrich, Gillingham, England, UK).…”
Section: Infection Assaymentioning
confidence: 99%
“…The current antimicrobial mixture using (Aq) was earlier shown to reduce N. messor virulence by avoiding actin polymerization and improving cell-membrane integrity. The antipathogenic mechanism includes increased SOD and CAT activity, lower H 2 O 2 levels and inactivation of the ERK signal transduction pathway [ 14 ]. Our study shows that, in the case of EHP infection, we have also observed increased CAT and SOD activity; however, the regulatory mechanism involves the inactivation of the NF-κB pathway by Aq, an effect caused by the reduction in H 2 O 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…The SGP cells were prepared [ 14 ] and characterised [ 18 ] as previously described. Briefly, the SGP cells were grown in 24 plastic well plates (Analab, Lisburn, UK) in the presence of 0.1% DMSO (Thermo-Fischer, Gloucester, UK) media supplemented with 20% fetal bovine serum (FBS), 100 µg penicillin, 8% shrimp head extract, 6% salt solution, 20 ng epidermal growth factor (Sigma-Aldrich, Gillingham, UK), and 10 U/mL human recombinant interleukin 2 (Sigma-Aldrich, Gillingham, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant was finally harvested and diluted appropriately with sterile distilled water and subsequently cultured on BCYE-α agar. The cytotoxicity of Citrox BCL was determined as previously described [ 20 ] using the MTT assay (Sigma-Aldrich, Gillingham, England, UK).…”
Section: Methodsmentioning
confidence: 99%